2007
DOI: 10.1182/blood-2007-06-097238
|View full text |Cite
|
Sign up to set email alerts
|

The role of FDG-PET scans in patients with lymphoma

Abstract: 18-Fluoro-deoxyglucose positron emission tomography (FDG-PET) is a noninvasive, 3-dimensional imaging modality that has become widely used in the management of patients with malignant lymphomas. This technology has been demonstrated to be more sensitive and specific than either 67

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
175
1
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(198 citation statements)
references
References 86 publications
1
175
1
21
Order By: Relevance
“…26 Fluorine 18 fluorodeoxyglucose-PET is important in staging of lymphoma; FDG-PET leads to a change in stage of disease in up to 20% to 40% of patients, and in 5% to 15% of patients, this changes the treatment choice. [27][28][29][30][31][32][33][34][35][36][37] At present, the use of FDG-PET scans in the staging of lymphoma is the standard of care in most patients.…”
Section: Current Use Of Pet Scans In Managing Lymphoma Stagingmentioning
confidence: 99%
“…26 Fluorine 18 fluorodeoxyglucose-PET is important in staging of lymphoma; FDG-PET leads to a change in stage of disease in up to 20% to 40% of patients, and in 5% to 15% of patients, this changes the treatment choice. [27][28][29][30][31][32][33][34][35][36][37] At present, the use of FDG-PET scans in the staging of lymphoma is the standard of care in most patients.…”
Section: Current Use Of Pet Scans In Managing Lymphoma Stagingmentioning
confidence: 99%
“…Diffuse high FDG uptake of the bone marrow can occur due to the reactive changes of chemotherapy or the use of Colony-stimulating Growth factors (CSGF), in our study we insisted that the patient do not receive chemotherapy or CSGF at least two weeks prior to their PET scan. On the other hand, minimal bone marrow disease may be missed by FDG-PET, and thus FDG-PET should not be considered a replacement for bone marrow biopsy [13][14][15]. Conversely, mass lesions identified by CT may present as negative by PET.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that PET alone cannot replace CT for the purposes of pretreatment staging of lymphoma. Positive predictive value of FDG in aggressive NHL and HL are middle-range of value (80 and 50%, respectively), these values are substantially higher than the corresponding values for CT (about 40 and 20%, respectively [14][15][16][17], suggesting that FDG-PET is more accurate than CT in the response assessment of lymphoma. The low accuracy of CT is mainly due to the fact that CT cannot distinguish residual active tumor from inactive fibrosis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Various groups have used care-dose CT without the injection of intravenous iodinated contrast agent for attenuation, correction, or anatomical correlation. Previous studies revealed that 18 F-FDG PET-CT has a higher sensitivity and specificity than CE-CT in the evaluation of HL and high-grade NHL (3,4,(7)(8)(9)(10)(11). Moreover, several studies have suggested that PET imaging with care-dose unenhanced CT alone might be sufficient for staging, therapy monitoring, or follow-up in patients with HL and aggressive NHL, except in special cases (7,12).…”
Section: Discussionmentioning
confidence: 99%
“…This provides a significant advantage for the evaluation of lymphoproliferative malignancies, particularly for the detection of lymphomatous involvement in organs and nodes of normal size without any mass. Several studies suggest that the sensitivity and specificity of 18 F-FDG PET-CT for the assessment of nodal and extranodal involvement were higher than those of standard contrast-enhanced CT (CE-CT) (3,4,(7)(8)(9)(10)(11). These benefits make 18 F-FDG PET-CT the standard imaging technique for the initial staging, therapy response evaluation and restaging of patients with lymphoma.…”
mentioning
confidence: 99%